Cardiovascular complications in non-cardiac surgery: what remains out of sight? - S. S. Murashko; S. A. Berns; I. N. Pasechnik (Кардиоваскулярная терапия и профилактика, 2024)
Aim. To evaluate any cardiovascular abnormalities in the postoperative period, their prevalence and impact on the course of postoperative period in patients after non-cardiac surgery, which underwent postoperative examinations of cardiovascular system.Material and methods. The study included 2937 patients. The assessed end points were postoperative cardiovascular events (CVEs). Along with major adverse cardiovascular events (MACE), we analyzed any cardiovascular abnormalities in the postoperative period as follows: electrocardiographic ST-T abnormalities, acute or decompensated heart failure (HF), arrhythmias, episodes of hypotension or hypertension, bleeding, thromboembolic events (TEEs), cerebrovascular events, postoperative delirium. Any CVEs constituted the any cardiovascular events' (ACVEs) group. Statistical analysis was carried out using the StatTech v program. 3.1.6 (OOO Stattekh, Russia).Results. Any postoperative complications according to the Clavien-Dindo classification were 54,7%, while grade 1 — 33,9%, grade 2 — 20,3%, grade 3 — 1 case, grade 4 — 0,4%, grade 5 — 0,1%. MACEs developed in 0,2% of cases. ACVEs amounted to 13,3%, including 2,3% — ST-T abnormalities, 6,3% — significant systolic blood pressure changes, 2,6% — arrhythmias, 0,7% — HF, 2,4% — bleeding, 1,1% — TEEs, 0,3% — delirium. In addition, 67 (17,5%) patients had ≥2 CVEs. Comparison of the length of hospital stay of patients with ACVEs, in particular with MACEs, ECG ST-T abnormalities, HF, arrhythmia, episodes of hypotension or hypertension, bleeding, TEEs, cerebrovascular events, delirium, with groups of patients without such complications revealed significant differences. ACVEs accounted for 1/4 of all postoperative complications and 2/3 of complications of grades 2-5.Conclusion. We expanded the concept of CVEs, united the totality of any cardiovascular abnormalities in the postoperative period, emphasized not only their clinical significance, but also the economic feasibility of taking into account ACVEs.